# Solve by using the quadratic formaula. Put answers in exact value, simplest radical form where applicable. 6x squared - x - 2 = 0

*print*Print*list*Cite

Expert Answers

sciencesolve | Certified Educator

You need to solve for x the quadratic equation `6x^2 - x - 2 = 0` , using the following quadratic formula, such that:

`x_(1,2) = (-b +- sqrt(b^2 - 4ac))/(2a)`

Identifying the coefficients a,b,c yields:

`a = 6, b = -1, c = -2`

`x_(1,2) = (-(-1) +- sqrt((-1)^2 - 4*6*(-2)))/(2*6)`

`x_(1,2) = (1 +- sqrt(1+48))/(12)`

`x_(1,2) = (1 +-7)/12 => x_1 = 2/3; x_2 = -1/2`

**Hence, evaluating the solutions to the given quadratic equation, using quadratic formula, yields **`x_1 = 2/3; x_2 = -1/2.`